Development of a Handover Model in Medical Services to Improve Service Quality at Hospital X Cikarang - Listia Evalina; Rokiah Kusumapradja; Tjipto Rini; Aytan Azizli (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the clinical handover process as a critical component of patient safety and healthcare service quality in hospital settings. Inconsistent communication, incomplete documentation, and the absence of standardized procedures were identified as major problems contributing to communication failures and potential adverse events. The objective of this research was to develop and test a structured and effective handover model that could improve communication accuracy and documentation reliability among healthcare professionals. A mixed methods design was employed, consisting of a qualitative phase (in-depth interviews, observations, and document analysis) to explore real-world handover practices, followed by a quantitative phase using a pretest–posttest design to evaluate the effectiveness of the proposed model. The study proposes an integrated handover model based on SBAR-IM (Situation, Background, Assessment, Recommendation, Intervention, Monitoring) strengthened by Quality Control (QC) and Mutual Confirmation (MC) mechanisms. The findings demonstrate a significant improvement in handover quality after implementation, with communication scores increasing from 74 to 84.5 and documentation scores improving from 48.3 to 63.0 (p < 0.05). Qualitative results further revealed reduced communication errors, improved clarity of clinical information, and enhanced interprofessional collaboration. This study concludes that the proposed SBAR-IM–based QC–MC model is effective, practical, and suitable for improving patient safety and healthcare service quality in hospital environments.